Effects of dance on the attention of children with autism - Manalac, Megan Marie C.; Magtoto, Frances Olivia M.; Echavia, Darlene D.; Dimarucut, Alberto L. (Quezon City College of Education, University of the Philippines Diliman, 2021)
This study aimed at describing the attentional needs of six (6) male students diagnosed with autism and exploring the use of line dance inside the classroom. Observations on whether line dancing was beneficial or served as barrier to the attentional needs of the children with autism (CWA) were also noted. Qualitative data was gathered through observations and anecdotes. In addition, the presence and frequency of the measured behavior were noted using a researcher-generated observation checklist. The study adopted a single-subject case design, following a baseline-intervention-baseline method of gathering data, wherein Days 1-5 and 21-25 of Phase Il were the baselines, and Days 6-20 served as the intervention phase. Findings of the study showed that the use of line dance inside the classroom addressed the attentional needs of the children with autism at varying degrees. In this study, target behavior referred to showing: (1) more on-task behavior, (2) skill in listening and following directions, and (3) less time resisting. But it is to be noted that total elimination of negative behavior was not the objective of the study. Further, the study noted the benefits of the intervention on the participants and its barriers to their behavior. Further findings showed that certain external factors may have caused the negative behavior manifested by the student participants. With the favorable outcome of the intervention, it is suggested that dancing be integrated in daily activities of CWA, or even the general population. It is recommended that dancing be considered as an effective strategy in addressing the attentional needs of CWA, but with several considerations for similar and future studies.
Thesis
Includes bibliographical references (pages 113-119)
Keywords: Children with disabilities -- Education -- Philippines; Autistic children -- Education -- Philippines; Dance therapy for children; Children with autism spectrum disorders -- Behavior modification .; Attention-deficit-disordered children